2005
DOI: 10.1016/j.icesjms.2005.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of multiple management objectives for Northeast Atlantic flatfish stocks: sustainability vs. stability of yield

Abstract: This paper describes a simulation study that evaluated the ICES scientific advisory process used to recommend total allowable catches (TACs) for flatfish stocks. Particular emphasis is given to examining the effects on stock biomass, yield and stability of constraining interannual variation in TACs. A “management strategy evaluation” approach is used where an operating model is used to represent the underlying reality, and pseudo data are generated for use within a management procedure. The management procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 14 publications
2
38
0
Order By: Relevance
“…The main factor that could contribute to this analysis would be the accuracy of predictions of location choice based on knowledge of the two main target species, bearing in mind the fact that fisheries have historically been managed on a stock-by-stock basis. Although several studies have been published on the North Sea sole and plaice fishery (Kell et al, 1999(Kell et al, , 2005Ulrich et al, 2007;Kraak et al, 2008;Andersen et al, 2010), the work reported here on the spatial dynamics of the fleet may complement future research effort, as it has in other MSE spatial studies (Pelletier and Mahévas, 2005;Bastardie et al, 2010;Lehuta et al, 2010). Such an analysis could provide an insight into mixed fishery management, because in the short term, an approach needs to be developed to resolve conflicting management advice for different species in the same fishery.…”
Section: Discussionmentioning
confidence: 93%
“…The main factor that could contribute to this analysis would be the accuracy of predictions of location choice based on knowledge of the two main target species, bearing in mind the fact that fisheries have historically been managed on a stock-by-stock basis. Although several studies have been published on the North Sea sole and plaice fishery (Kell et al, 1999(Kell et al, , 2005Ulrich et al, 2007;Kraak et al, 2008;Andersen et al, 2010), the work reported here on the spatial dynamics of the fleet may complement future research effort, as it has in other MSE spatial studies (Pelletier and Mahévas, 2005;Bastardie et al, 2010;Lehuta et al, 2010). Such an analysis could provide an insight into mixed fishery management, because in the short term, an approach needs to be developed to resolve conflicting management advice for different species in the same fishery.…”
Section: Discussionmentioning
confidence: 93%
“…Butterworth et al, 1997;Butterworth and Punt, 1999;Cooke, 1999;Kell et al, 1999Kell et al, , 2005. Harvest strategies consist of the following components: data collection schemes, assessment methods, and harvest control rules (HCRs, Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…One issue that we did not discuss here is about the role implementation time (time lag between the time the HCR is applied and the time when the corresponding management measures is implemented) plays in the development of HCR. We chose not to explore that aspect here mainly because of the complexity of such discussion, which can include issues such as accuracy of implementation, accounting correctly for the time lag in the HCR, the purpose of management feedback, etc., but also because this topic has been the focus of other published work (Kell et al 2005;Loehle 2006). …”
Section: Discussionmentioning
confidence: 98%